Health care provider experiences in primary care memory clinics: a phenomenological study - Sheiban, Linda (BMC Fam Pract, 2018)
BACKGROUND: There is a growing need for community-based services for persons with Alzheimer’s disease and related dementias (ADRD). Memory clinic (MC) teams in primary care settings have been established to provide care to people with ADRD. To consider wider adoption of these MC teams, insight is needed into the experiences of practitioners working in these models. The purpose of the current study is to explore the experiences of health care providers (HCPs) who work in primary care Memory Clinic (MC) teams to provide care to persons with Alzheimer’s disease and related dementias (ADRD). METHODS: This study utilized a phenomenological methodology to explore experiences of 12 HCPs in two primary care MCs. Semi-structured interviews were completed with each HCP. Interviews were recorded and transcribed verbatim. Colaizzi’s steps for analyzing phenomenological data was utilized by the authors. RESULTS: Three themes emerged from the analysis to describe HCP experiences: supporting patients and family members during ADRD diagnosis and treatment, working in a team setting, and personal and professional rewards of caring for people with ADRD and their family members. CONCLUSIONS: Findings provide insight into current practices in primary care MCs and on the motivation of HCPs working with persons with ADRD.